Structured Transition Protocol for Children with Cystinosis - Raina, Rupesh; Wang, Joseph; Krishnappa, Vinod (Frontiers in Pediatrics, 2017)
The transition from pediatric to adult medical services has a greater impact on the care of adolescents or young adults with chronic diseases such as cystinosis. This transition period is a time of psychosocial development and new responsibilities placing these patients at increased risk of non-adherence. This can lead to serious adverse effects such as graft loss and progression of the disease. Our RISE to Transition protocol will provide patients, families, physicians, and all those involved a structured guide to transitioning cystinosis patients. This structured protocol depends on four areas of competency: Recognition, Insight, Self-reliance, and Establishment of healthy habits (RISE). This protocol has not been tested and therefore challenges not realized. With a focus on medical, social, educational/vocational aspects, we aim to improve transition for cystinosis patients in all aspects of their lives.